THE TRANSLATION TECHNIQUES OF THE EXPRESSIVE UTTERANCES IN CAPTAIN AMERICA - F. Endy Sativa; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2021)
The objectives of the research were (1) to describe the expressive utterances in Captain Americamovie; and (2) to analyze the translation techniques used in translating expressive utterances inCaptain America movie. This research was qualitative and, therefore, descriptive too. Thesource of data was the English transcript of Captain America movie and its Indonesian subtitle.The data collection technique was document analysis while the data collection analysis wasetnographic. Five expressive utterances found in the script of the movie entitled CaptainAmerica: The first Avenger. They were denying, admitting, apologizing, congratulating, andthanking. The first two, namely denying and admitting, were the most dominant. The expressiveutterances were translated with twelve translation techniques, namely established equivalent,modulation, deletion, transposition, literal translation, adaptation, discursive creation, addition,explicitation, compensation, and generalization. Establihed equivalent was the most dominanttranslation technique.Keywords: Captain America Movie, Expressive Utterances, Translation Techniques